The Impact of The Tongue Twister Technique on The Speaking Ability of Students and Pronunciation: English - M. Hilmy Hidayatullah; Ukhtul Iffah; Rizqatin Mubarokah ZK (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
The purpose of this study was to gather empirical proof that tongue twisters significantly affect students' speaking abilities and pronunciation. This study employed a quantitative methodology and a quasi-experimental research design. This study was carried out at SMP NAA Alasbuluh-Wongsorejo-Banyuwangi in the eighth grade. The experimental class (38 students) and the control class (41 students) were the two groups in the researcher's basic random sampling technique. The researcher employed a tongue twister test as the tool for data collection, and the students' speaking and pronunciation on the pre-test and post-test were scored using a speaking and pronunciation scoring rubric. The experimental class's post-test mean score, as determined by the t-test calculations, was 80.68, whereas the control class's was 50.65. In the statistical hypothesis test, robserved (0.958) was greater than rtable (0.2213) at the 5% significance level. It indicates that the null hypothesis was rejected and the alternative the hypothesis (Ha) was accepted. It was demonstrated that the tongue twister approach affects eighth-grade students' speaking and pronunciation at SMP NAA Alasbuluh-Banyuwangi